Climacocystaceae fam. nov. and Gloeoporellaceae fam. nov., two new families of Polyporales (Basidiomycota) - Liu, Shun; Zhou, Jun-Liang; Song, Jie; Sun, Yi-Fei; Dai, Yu-Cheng; Cui, Bao-Kai (Frontiers in Microbiology, 2023)
The Polyporales is a diverse group of Agaricomycetes including more than 2500 species belonging to 255 genera and 18 families. Recently, many studies focused on the classification of Polyporales, but the familial placements of some taxa remain uncertain. In this study, two new families: Climacocystaceae and Gloeoporellaceae of Polyporales are proposed based on morphological characters and molecular data. Phylogenetic analyses of the two new families are inferred from the DNA sequences of the internal transcribed spacer regions (ITS), the large subunit of nuclear ribosomal RNA gene (nLSU), the largest subunit of RNA polymerase II gene (RPB1), the second largest subunit of RNA polymerase II gene (RPB2) and the translation elongation factor 1-α gene (TEF1). Furthermore, the divergence time of Polyporales was estimated as an additional taxonomic criterion based on the conserved regions of five DNA fragments (5.8S, nLSU, RPB1, RPB2 and TEF1). Bayesian evolutionary analysis revealed that the ancestor of Polyporales split with a mean stem age of 136.53 Mya with a 95% highest posterior density (HPD) of 118.08–158.06 Mya. The mean stem ages of the families within Polyporales originated between 66.02 to 119.22 Mya, of which Climacocystaceae occurring in a mean stem age of 77.49 Mya with a 95% HPD of 61.45–93.16 Mya, and Gloeoporellaceae occurring in a mean stem age of 88.06 Mya with a 95% HPD of 67.15–107.76 Mya.